Formulasi Sediaan Granul Mukoadhesif Kombinasi Ekstrak Kulit Batang Mimba (Azadirachta indica A. Juss) dan Kunyit (Curcuma domestica val.) - Sutriyo, Sutriyo; Khairunnisya, Khairunnisya; Mun’im, Abdul (UI Scholars Hub, 2011)
Neem bark (Azadirachta indica A.Juss) and turmeric (Curcuma domestica Val.) extracts have been found posses gastroprotective effect so that they are used in the treatment of gastric ulcer. Administration of combination of both extracts can give synergistic effect so that the administration dose can be reduced. In this research, combination of neem bark and turmeric extracts were formulated as mucoadhesive granules to improve their effectivenesses by increasing the residence time of dosage form in the stomach. Mucoadhesive granules were prepared by wet granulation method in six formulas using HPMC, Carbopol, and combination of HPMC and Carbopol as mucoadhesive polymers. Granules were evaluated for particle size distribution, swelling, mucoadhesive strength with bioadhesive in vitro test and wash off test, and dissolution. Bioadhesive in vitro test showed that all formulas have goodmucoadhesive strength.Wash off test showed that combination of HPMC and Carbopol can improve mucoadhesive strength of formulas. Mucoadhesive strength increased with the increasing of HPMC. The result of this research indicated that formula with combination ofHPMCand Carbopol (2:1) showed best mucoadhesive strength with percentage of mucoadhesion 98.67%in bioadhesive in vitro test and 38.00% in wash off test.